Tumor irradiation combined with minimally invasive surgery (vascular-targeted photodynamic therapy) enhances anti-tumour effects in preclinical prostate cancer - Sjoberg, Hannah (Journal of the Nuffield Department of Surgical Sciences, 2021)
Hanna T Sjoberg, Yiannis Philippou, Anette L Magnussen, Iain DC Tullis, Esther Bridges, Andrea Chatrian, Joel Loefebvre, Ka Ho Tam, Emma A Murphy, Jens Rittscher, Dina Preise, Lilach Agemy, Tamar Yechezkel, Sean C Smart, Paul Kinchesh, Stuart Gilchrist, Danny P Allen, David A Scheiblin, Stephen J Lockett, David A Wink, Alastair D Lamb, Ian G Mills, Adrian Harris, Ruth J Muschel, Boris Vojnovic, Avigdor Scherz, Freddie C Hamdy, Richard J Bryant. Introduction There is an important clinical need to improve the treatment of high risk localised and locally advanced prostate cancer (PCa), and to reduce the side effects of these treatments. We hypothesised that multi-modality therapy combining radiotherapy and vascular-targeted photodynamic therapy (VTP) could PCa tumour control compared against monotherapy with each of these treatments alone. This could provide proof-of-concept to take to the clinic. VTP is a minimally invasive focal surgical therapy for localised PCa, which rapidly destroys targeted tumours through vascular disruption. Tumour vasculature is characterised by vessel immaturity, increased permeability, aberrant branching and inefficient flow. Fractionated radiotherapy (FRT) alters the tumour microenvironment and promotes transient vascular normalisation. Materials and Methods We investigated whether sequential delivery of FRT followed by VTP 7 days later improves PCa tumour control compared to monotherapy with FRT or VTP alone. Results FRT induced vascular normalisation changes in PCa flank tumour allografts, improving vascular function as demonstrated using dynamic contrast enhanced magnetic resonance imaging. FRT followed by VTP significantly delayed tumour growth in flank PCa allograft pre-clinical models, compared with monotherapy with FRT or VTP alone, and improved overall survival. Conclusion Taken together, these results suggest that combining FRT and VTP could become a promising multimodal clinical strategy in PCa therapy. This provides proof-of-concept for this multi-modality therapy approach to take forward to early phase clinical trials.